Ministering effectively in the context of Pentecostalism in Africa: A reformed missional reflection - Mashau, Thinandavha D. (In die Skriflig/In Luce Verbi, 2013)
Pentecostalism is a global phenomenon with a large following in North America, Latin America, Asia, Africa and other parts of the world. The rise, growth and influence of Pentecostalism in Africa are enormous and have, without fear of contradiction, become one of the dominant expressions of Christianity on the continent. A contextual analysis of Christianity in Africa showed that the African soil is more fertile for this movement. Its manifestation ranges from classical Pentecostalism (first wave), to the charismatic movement (second wave) and the charismatic renewal movements (third wave). Its growth in Africa came with a fair number of missiological challenges to evangelical reformed churches, and therefore this article sought to sketch this movement by providing a historical perspective on Pentecostalism, a contextual analysis of Pentecostalism in Africa, issues and challenges in Pentecostalism, and concludes by looking closely at a reformed missional reflection, thereby providing some nuances as to how best one can minister effectively in the context of Pentecostalism. This article called for evangelical reformed churches to exercise the spirit of discernment whilst dealing with the influence of Pentecostalism, but at the same time to learn from this movement the zeal for mission and the role of the Holy Spirit in mission. Reformatoriese missionale nadenke oor effektiewe bediening in the konteks van Afrika Pentekostalisme. Pentekostalisme is 'n globale fenomeen met ‘n groot aanhang in Noord-Amerika, Latyns Amerika, Asië, Afrika en ander wêrelddele. Die opkoms, groei en invloed van Pentekostalisme in Afrika was geweldig en het een van die dominante gedaantes van Christenskap op die kontinent geword. ‘n Kontekstuele analise van Christenskap in Afrika wys dat Afrika meer vatbaar was vir hierdie tendens. Die manifestasie daarvan reik van klassieke Pentekostalisme (eerste golf), tot die charismatiese beweging (tweede golf) en die charismatiese herlewingsbewegings (derde golf). Die groei hiervan het ’n goeie aantal missiologiese uitdagings meegebring vir evangeliese gereformeerde kerke. Gevolglik het hierdie artikel gepoog om die tendens uit te wys deur ’n historiese perspektief op Pentekostalisme te bied, gevolg deur ’n kontekstuele analise van Pentekostalisme in Afrika, ’n bespreking van vraagstukke en uitdagings binne Pentekostalisme, en ter afsluiting ’n gereformeerde missiologiese oorweging hiervan, met klem op hoe bediening die beste kan plaasvind binne die konteks van Pentekostalisme. Die artikel het evangeliese gereformeerdes opgeroep om ’n gees van onderskeiding te openbaar wanneer hulle te doen kry met Pentekostalisme terwyl hulle terselfdertyd uit hierdie groep se ywer met sending en die rol van die Heilige Gees daarin geleer het.
free